Source of sugar-sweetened beverages consumption among Indonesian: A mini review - Sifa Aulia Wicaksari (Ikatan Sarjana Gizi Indonesia (ISAGI), 2022)
Overweight-obesity become global health concern and sugar sweetened beverages is highlighted contributing the excessive energy intake. This mini review aims to describe the source of sugar intake from beverage among Jakarta population as capital city of Indonesia. This study was mini review of 5 articles of SSB consumption using 7-days fluid record or semi quantitative food frequency questionnaire (SQFFQ). This study obtained the information that SSBs consumption has occurred in younger age and increased in older age. SSBs consumption is dominated by milk-based drinks in children, milk-based drink and flavored beverages such as carbonated soft drinks, electrolyte drinks, sport drinks, flavored drinks (not include original fruit drinks) in adolescence, and milk-based drinks, tea and coffee-based drinks in young adults. It is necessary to educate the care giver for children and adolescents also young adults regarding the healthier beverages to prevent health impacts due to SSBs consumption.